Możliwości pracy naukowej na pograniczu – na przykładzie badań środowiska kościelnego - Tereza Ondruszová (Postscriptum Polonistyczne)
The article briefly presents activities of The Department of Polish Studies at the University of Ostrava. It also calls attention to the main fields of interests of the author of the article who represents the young generation of Czech polonists. While concentrating on her research, the author investigates the areas of contact between Polish and Czech languages within the church community in Zaolzie (Czech Republic). She analyses the results of the survey conducted amongst the believers and priests in that region as well as the recordings of the sermons preached by the Roman Catholic priests in Zaolzie.